Physical Condition Profile of Male Volleyball Athletes for the 2025 Magelang Regency Pre-Provincial Athletics Competition - Damar Adi Susetyo; Agung Wahyudi (Universitas Negeri Semarang, 2025)
This study aims to determine and analyze the physical condition profile of male volleyball athletes participating in the Magelang Regency Pre-PORPROV. The physical condition components analyzed include arm muscle strength, back muscle strength, leg muscle power, and cardiorespiratory endurance. The study used a quantitative approach with a survey method. The research subjects consisted of 14 male volleyball athletes from the Magelang Regency Pre-PORPROV team. The measurement instruments used were push-ups, back-ups, vertical jumps, and beep tests. Data analysis used a quantitative descriptive approach with normative categorization. The results showed that the overall physical condition profile of the male volleyball athletes of the Magelang Regency Pre-PORPROV team was in the moderate category (42.86%). Component analysis showed that arm muscle strength was in the good category (50%), back muscle strength was in the moderate category (42.86%), leg muscle power was in the moderate category (57.14%), and cardiorespiratory endurance was in the moderate category (35.71%). This study recommends a more structured training program with an emphasis on improving cardiorespiratory endurance and leg muscle power to maximize the athletes' performance in facing the PORPROV competition.